The Challenges of Managing a Diverse Workforce - XIA, YU (2017)
Abstract Along with current professional migration trends, growth of globalization and booming of multinational organizations, the composition of employees has become more diverse than ever before, which is a challenge for most organizations. This study attempts to investigate the challenges of diverse employee management within an organization. The complexity of management lies in the fact that heterogeneity of diverse employees has two sides, namely advantages and disadvantages. Although many literature and research have investigated this area, they have limitations on the subject and methods used; and thus, are not enough for to understand and grasp the profound connotations surrounding this subject. This study is conducted with the qualitative method. Six participants from different organizations were interviewed. The result attained shows that although diverse workforce satisfies urgent requirements of employee shortage, it also brings challenges to management. Organizations may need to find better exploitation modes after experiencing long-term practices, depending on personality, attitude and work culture of employees and employers. Nowadays, organizations, especially transnational organizations (i.e. MNC) have great desires for overseas talents which possess better expertise, i.e. top higher education and professional qualification than ever before. The diversification of employees has double effects on an organization. On the one hand, more and more advanced talents can enhance the organizational competitiveness. On the other hand, Saxena (2014) indicated that everyone is different in many aspects (education, sex, ethic, race and so on), and thus diversity workforce may bring difficulties in human resource management and other in strategy implementations. This development tendency has put forward newer and higher requirements to human resource management within an organization, which include new ideas, new knowledge and new technology (Thite, et al., 2014).